P312 fMRI analysis of the human brain's neuroplasticity as a basis of movement disorders compensation after traumatic brain injury. Issue 9 (September 2017) - Sharova, Elena; Boldyreva, Galina; Chelyapina, Marina; Smirnov, Alexander; Azarov, Anton; Mukhina, Tatiana; Gavron, Alexsey; Kulikov, Michael; Alexandrova, Evgenia; Pronin, Igor
Abstract : Severe traumatic brain injury (STBI) is nearly always comes with movement disorders. Objectives: Comparison of cerebral structural-functional control of movement's opportunity and implementation in healthy volunteers and patients with various degrees of hemiparesis after STBI. Methods: Observation groups: 28 patients with SOBI (main) and 17 healthy volunteers (control). 3T fMRI recorded at rest and passive right hand finger clenching (by experimenter). Individual and group analysis of Sensorimotor resting-state network and motor fMRI responses was carried out by FSL software (ICA algorithm), SPM8 and CONN. Topography and volume activated brain regions as well as brain connectivity between them were determined. Results: At STBI in the majority cases without hemiparesis or with its mild degree, neuroanatomy of the rest-state sensorimotor network and "passive" motor fMRI response are close to normal. However with an increase of hemiparesis expression we have seen an asymmetric reduction of sensorimotor resting-state network and more diffuse "passive" fMRI response - with activation of nonspecific to movement brain structures: frontal and temporal cortex, cerebellar vermis and others. Discussion: A comparison of the passive movement's functional anatomy in STBI with motor system topographic anatomy indicates a variability in movement disorders compensation mechanisms based on the possible inclusion of different "functional doublers", such as fronto-pontinus conduction tract as well as occipito–temporopontinus. This hypothesis confirmed by comparative analysis of brain connectivity within different neuroanatomical motor tracts in healthy volunteers and patients with STBI. Conclusions: The retrieved data can be useful to develop individualized neurorehabilitation programs of post-traumatic motor disorders. Supported by RFFI 115-36-01038.